Determinants of Cross-Border Informal Trade: The Case of Benin - Bensassi, Sami; Jarreau, Joachim; Mitaritonna, Cristina (International Food Policy Research Institute, 2016)
This paper utilizes a survey on informal cross-border trade in Benin (ECENE), conducted by the National Institute of Statistics in 2011, to study the determinants of informal versus formal trade, concentrating on Benin’s exports and re-exports to neighboring countries. We first show that goods traded formally and informally are very different and that the overlap between the two types of trade is very thin, suggesting the existence of two separate channels of trade. For example, agricultural products are mainly traded informally. Second, we illustrate how including informal cross-border trade gives to regional trade a higher role compared to that measured using formal trade only, which is particularly low by global standards. Finally, we study trade policy variables, and the time sensitiveness of products, as potential determinants of informality. We find that trade policy variables (tariffs and import bans) significantly explain informality of trade. We also find that, for re-exports, time sensitive products are more likely to be traded through the informal channel. This suggests a potential role for trade facilitation measures in reducing informality.